Pengaruh Quality of Work Life dan Motivation terhadap Employee Performance (Studi Kasus Pegawai Desa Cidahu Kabupaten Sukabumi) - Wahyu Indra Gunawan; Lusi Fauzianingsih (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2018)
This study aims to determine: (1) the influence of quality of work life on employee performance, (2) the influence of motivation on employee performance, and (3) the effect of quality of work life and motivation simultaneously on employee performance. The subject of this research is all employees of Village Office Cidahu located in Cidahu Kabupaten Sukabumi. The number of respondents in this study as many as 63 people. Methods of data collection through surveys using questionnaires. Data analysis technique used in this research is Multiple Linear Regression Analysis. The results show that (1quality of work life has no effect on employee performance. (2) motivation positively affects employee performance. 3) simultaneously quality of work life and motivation positively affect employee performance. Further research is needed by this Village Office Cidahu so that employees are able to produce high performance.